Operational risk factors in agriculture: Evaluation through the Analytical Hierarchical Process (AHP) method. Case study on the coffee crop - Quiros Badilla, Diego Fernando (2020)
The objective of this study was to determine a weighted value of the importance of the sources of operational risk in agriculture, as well as the factors that compose them. Besides, operational risk events applied to a case study in coffee production (Coffea arabica) in Costa Rica were identified. The panels were used for the application of the analytical hierarchy process method (AHP) to obtain the weight of importance concerning the risk of the sources and operational risk factors, likewise, a second panel was implemented under the same structure obtained by the AHP method for the determination of risk events in the selected crop. The results obtained determined that, in general, climatic and environmental factors are the riskiest (55.96%), followed by production processes (24.95%), while human resource management and production technologies have the same weight (9.55%). Weight was obtained for each proposed risk factor and 79 risk events were identified in the coffee crop under this same structure. This study allowed us to prioritize the components of operational risk in agricultural production systems, a concept that had not been previously analyzed in the agricultural sector; and allowed the generation of a solid structure for the identification of specific risk events.